(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider a mixed boundary value problem to a class of nonlinear operators containing p(·)-Laplacian. More precisely, we are concerned with the problem with the Dirichlet condition on a part of the boundary and the Steklov boundary condition on an another part of the boundary. We show the existence of at least three weak solutions under some hypotheses on given functions and the values of parameters.